ON QUASI NEWTON METHOD FOR SOLVING FUZZY NONLINEAR EQUATIONS - Umar A Omesa; Mustafa Mamat; Ibrahim M Sulaiman; Sukono Sukono (International Journal of Quantitative Research and Modeling, 2020)
This paper presents Quasi Newton’s (QN) approach for solving fuzzy nonlinear equations. The method considers an approximation of the Jacobian matrix which is updated as the iteration progresses. Numerical illustrations are carried, and the results shows that the proposed method is very encouraging.